As relações interpessoais em redes de apoio ao terceiro setor - Reyes Junior, Edgar (Universidade do Vale do Rio dos Sinos, 2012)
The social relationships are an essential element for the effectiveness of interorganizational relationships. Although not a clear concept, there is a strong relationship between trust and social interaction processes in which occur shared values. The social relationship can evolve toward friendships or acquaintance. Trust can also be mediated by the perception of others, which is a mechanism of interpersonal reputation, rather than the direct interaction between the parties. This set of relationships differentiates the network actors in their relational power. The third sector is comprised of nonprofit organizations that do not belong to the sphere of the State or the market. These nonprofits are created and maintained through voluntary participation and aim to continue the traditional practice of philanthropy. They are next to the local communities to understand their needs. These social relationships can influence the support for the third sector. The objective of this research was to understand how to establish socially trust in a network of supporting institutions to the third sector. To achieve this objective it was necessary to analyze the relationship between supporters and institutions of the third sector; to identify the structural aspects of the network of supporters of third sector institution; to verify the formative elements of social relations in the network; and to analyze features determinants of reputation actors in the network. Thirty-three supporters of Parceiros Voluntários from Bento Gonçalves were interviewed. The critical incident technique and social network analysis were used to analyze the data collected in interviews. There were different reasons for supporting the third sector organizations, which can be defined as institutional, personal and rational reasons. the presence of a local entity gives credibility to the organization of the third sector. The central actors in the network are also connected to social institutions. Actors in a network are grouped from particular characteristics of these individuals. About social relations, initially there is a clear difference between friendship and acquaintance. Self revelation is the element that distinguishes the relations of friendship and acquaintance. While the affective aspects predominate in the first, utilitarianism is this acquaintance. The characteristics that involve social relationships can be divided in to those that generate the relationship and those who make them evolve. The similarity of behavior is distinguished as the main factor that allows the rapprochement between people. Honesty, while reducing opportunistic behavior also manifests itself important. Complementarity and network relationships are important to bring actors in relations of acquaintance. To consolidate relations, the availability of time and to serve the constant socializing, counseling and respect are the predominant features for both for relations of friendship, and for the acquaintance.
Keywords: Terceiro setor; Relações sociais; Confiança; Redes interorganizacionais; Third sector; Trust; Social relationship; Interorganizational networks; ACCNPQ::Ciências Sociais Aplicadas::Administração